Fourteenth Century England XII. - Bothwell, James; J. S. Hamilton, Jeffrey S.; Dryburgh, Paul; Gaite, Pierre; Given-Wilson, Christopher; Jones, Michael C. E.; Kniphfer, Taylor; Lane, Samuel; Mackman, Jonathan; McHardy, Alison K. (Fourteenth Century England, 2022)
Essays offer a lively snapshot of important topics.